Avaliação da funcionalidade de atletas de basquete sobre rodas com lesão medular na perspectiva da Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF) - Benatti, Danyelle Fernanda de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Introduction: Spinal cord injury occurs due to interuption in nerve stimuli and could caused from traumatic and non-traumatic illnes. After spinal cord, there are problems in personal life activities affecting ou modifying personal life and provoking impacts in his own life. International Classification of Functioning, Disability and Healthy (ICF) consider and analyse more than the illness ou injury and include informations about functionality in differents domains as activities, participation and enviroment. Objective: The aim of this study is to evaluate functionality wheelchair athlets with spinal cord injury using ICF. Metodology: For this research, it was evaluated 60 athlets with spinal cord injury who were practicing wheelchair basqketball, using the Checklist corresponding to the main ICF categories and othes Identity Protocol with personal datas, lesion time, lesion level and functional classification from bwheelchair basketball. Results: In analyses, we identify in quartis data, that in Body Fucntion, median was 56,67% from all athlets with light and moderate qualifications; In Body Strutucture, the median was 60% for light qualifications; in Activities and Participation, this median corresponded to 91% and in Enviroment Factors, 51,67% feel that this enviroment was facilitator... (Complete abstract click electronic access below)

Introdução: A lesão medular ocorre devido à interrupção de estímulos nervosos que pode ser por causas traumáticas ou não traumáticas. Após a lesão medular, ocorrem comprometimentos de atividades da vida da pessoa, afetando ou modificando sua vida e causando impacto na sua participação social. A Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF) contempla e analisa além da doença ou da lesão, inclui informações sobre a funcionalidade em diferentes domínios tais como atividades, participação e ambiente. Objetivo: o Avaliar a funcionalidade de atletas de basquete sobre rodas com lesão medular, utilizando a CIF. Metodologia: Para a realização da pesquisa foram avaliados 60 atletas com lesão medular, praticantes de basquete sobre rodas utilizando um formulário denominado Checklist das principais categorias da CIF e uma ficha de identificação contendo dados pessoais, tempo da lesão, nível da lesão e classificação funcional do basquete. Resultados: Na análise dos dados, verificou-se que, a partir de quartis, na categoria Função do Corpo, a mediana foi de 56,67% dos atletas com qualificadores entre leve a moderado... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Fisioterapia; Basquetebol em cadeira de rodas; Traumatismos em atletas; Medula espinhal